Social Capital in American Life - Jones, Brian J. (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
Is American society falling apart? Put this provocative question to people you know and you will encounter a disturbing number of affirmative answers. But beyond such emotional foreboding, how would one factually answer the question? In this book, Brian J. Jones poses the issue by first building a theoretically-based model of the guts of any living society-family, work, voluntary association and social networks. This model of social capital is then tested using some four decades of real-world data from the General Social Survey, the gold standard for modern survey research. This process here yields real answers about life in America. People are reallocating their commitments to family and work, to friends and neighbors. These changes are tied to Americans' deepest motivations such as trust and happiness. Also unearthed are deep signs of societal divisions along the fault lines of education, marriage and race. Social Capital in American Life is a serious answer to a provocative-and very real-question.